1994
DOI: 10.1017/s1068280500000381
|View full text |Cite
|
Sign up to set email alerts
|

An Experiment in Contingent Valuation and Social Desirability

Abstract: Social desirability (SD) represents the problem of subjects responding with social norms rather than individual values. This paper briefly surveys the SD literature and considers its relevance for contingent valuation (CV) studies. In an empirical study, undergraduate students were administered the Mariowe-Crowne Social Desirability Scale, as well as CV questions. High SD scores were hypothesized to imply a greater likelihood of offering a protest reason for a zero bid and to increase bids for socially desirab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 13 publications
0
16
2
Order By: Relevance
“…These results -at least partly -contrast the findings of Laughland et al (1994). Those authors did not detect any direct relationship between need for social approval as assessed by the Marlowe-Crowne Scale and WTP statements.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…These results -at least partly -contrast the findings of Laughland et al (1994). Those authors did not detect any direct relationship between need for social approval as assessed by the Marlowe-Crowne Scale and WTP statements.…”
Section: Discussioncontrasting
confidence: 80%
“…The only study to our knowledge that employed this approach was done by Laughland et al (1994). The hypothesis that respondents with higher need for social approval as measured by the MarloweCrowne social desirability scale (Crowne and Marlowe, 1960) have a significantly higher WTP for socially desirable goods, such as improved food safety and landscape preservation, is not clearly supported by their data.…”
Section: Previous Approaches In Sdr Researchmentioning
confidence: 96%
See 1 more Smart Citation
“…3 Laughland et al (1994) provide a review of social desirability literature in the context of CV methods. SD implies that subjects are responding in compliance with social norms rather than reporting their individual values (Laughland et al, 1994). Provision of many environmental public goods (e.g.…”
Section: Background and Previous Literaturementioning
confidence: 99%
“…However, information about the ability of individual farmers or communities to take up tsetse control measures is limited (Laughland et al, 1994;Swallow and Woudyalew, 1994;Kamuanga et al, 2001) and has not taken cognisance of demand patterns and schemes to promote community or farmer participation. Intuitively, the provision of tsetse control techniques would not exclude the use of trypanocidal drugs, and recent studies carried out in The Gambia (Mugalla, 2000;Kamuanga et al, 2004) showed this to be true.…”
Section: Introductionmentioning
confidence: 99%